2017
DOI: 10.1186/s13256-017-1462-5
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus in a patient with glycogen storage disease type Ia: a case report

Abstract: BackgroundGlycogen storage disease type Ia is a genetic disorder that is associated with persistent fasting hypoglycemia and the inability to produce endogenous glucose. The development of diabetes with glycogen storage disease is exceedingly rare. The underlying pathogenesis for developing diabetes in these patients is unclear, and there are no guidelines for treatment.Case presentationWe describe a case of a 34-year-old woman of South Asian descent with glycogen storage disease type Ia, who developed uncontr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Several recent clinical trials indicated that SGLT2 inhibition is an effective strategy for diabetes mellitus and concluded that it (1) facilitates reduction of body weight and visceral fat, (2) prevents progressive kidney disease, and (3) improves liver function in non-alcoholic steatohepatitis (NASH) occurring with diabetes mellitus. All the complications mentioned above are also observed In GSD type Ia and a previous case report indicated that SGLT2 inhibitor improved diabetes mellitus in GSD type Ia [2].…”
mentioning
confidence: 72%
“…Several recent clinical trials indicated that SGLT2 inhibition is an effective strategy for diabetes mellitus and concluded that it (1) facilitates reduction of body weight and visceral fat, (2) prevents progressive kidney disease, and (3) improves liver function in non-alcoholic steatohepatitis (NASH) occurring with diabetes mellitus. All the complications mentioned above are also observed In GSD type Ia and a previous case report indicated that SGLT2 inhibitor improved diabetes mellitus in GSD type Ia [2].…”
mentioning
confidence: 72%
“…Cases of GSD1a combined with diabetes are reported relatively rarely. In fact, there have only been five reported cases of GSD1a with diabetes mellitus [ 14 , 15 ], including one middle-aged adult case, two young adult cases, and two pediatric cases. No sex difference has been reported for the onset.…”
Section: Discussionmentioning
confidence: 99%
“…The Annual Symposium of the Society for the Study of Inborn Errors of Metabolism has reported four cases of GSD1a patients with DM and pointed out that glycemic control can be achieved through the reduction of weight through strict diet control [ 15 ]. In addition, a 34-year-old South Asian obese female patient with GSD1a and DM demonstrated stable glycemia control after diet control and exercise for weight loss and administration of oral canagliflozin and acarbose [ 14 ]. In our case, the patient was an underweight adult female (BMI = 16.64 kg/m 2 ) who had no obvious insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological treatments have included insulin, sodium-glucose cotransporter-2 inhibitors, and glucosidase inhibitors. [6][7][8][9] In this case, the woman was not overweight and so she continued a low glycaemic index diet with carefully titrated uncooked corn starch at night to prevent hypoglycaemia. Low-dose insulin was used to control postprandial hyperglycaemia without hypoglycaemia.…”
Section: Case Historymentioning
confidence: 96%
“…Previous reports of GSD with diabetes have indicated that weight loss may be beneficial. Pharmacological treatments have included insulin, sodium–glucose cotransporter‐2 inhibitors, and glucosidase inhibitors 6–9 . In this case, the woman was not overweight and so she continued a low glycaemic index diet with carefully titrated uncooked corn starch at night to prevent hypoglycaemia.…”
Section: Answersmentioning
confidence: 99%